DISCRIMINATION AND HEALTH ACROSS THE LIFE COURSE - Thorpe, R.J. (Innov Aging, 2017)
There is a paucity of research that seeks to understand why race disparities in health across the life course remain elusive. One such explanation that has been garnering attention is discrimination. This symposium contains papers seeking to address the impact of discrimination on health or health disparities across the life course. First, Hargrove investigates the extent to which multiple dimensions of discrimination account for skin color disparities in hypertension among 976 African Americans adults in the Coronary Artery Risk Development in Young Adults Study. This author reports significant intragroup heterogeneity in the discrimination-health link. Second, Cobb and Thorpe examine the relationship between the frequency of everyday discrimination and pulse pressure among 7,181 Black, Latino, and White older adults who participated in the 2006/2008 Health and Retirement Study. These authors report that the frequency of perceived everyday discrimination may differentially affect pulse pressure of older Whites and Blacks. Third, Thomas examines the relationship between social class discrimination (SCD) and mental health among 627 Black adults in the Nashville Stress and Health Study. This author demonstrates that SCD impacts mental health across the life course. Finally, Byrd examines racial disparities in cognitive ability among 991 older black and white adults in waves 4 and 5 of the Americans’ Changing Lives Study. There was no impact of discrimination on race disparities in cognitive ability over time. These presentations collectively bolster our knowledge of how discrimination impacts health and health disparities across the life course.